Effect of anthropogenic activity on benthic macroinvertebrate functional feeding groups in small streams of West Sumatra, Indonesia - Sudarso, Jojok; Suryono, Sri; Yoga, Gunawan P.; Imroatusshoolikhah,; Ibrahim, Aiman; Laela Sari,; Badjoeri, Muhammad; Samir, Octavianto (Universiti Kebangsaan Malaysia, 2022)
Functional feeding groups (FFG) of benthic macroinvertebrates have been used to characterize the condition of aquatic ecosystems, changes in land use, and assess the river health ecosystems. Ranggeh River belongs to a small river that plays a vital role in breeding the native fish of Lake Maninjau (West Sumatra). Agricultural activities and human settlements around the Ranggeh River can threaten life and change the FFG of benthic macroinvertebrates. This study aims to analyze and observe changes in water quality by anthropogenic activities and their impact on FFG benthic macroinvertebrates in a small stream (Ranggeh River). This research was conducted at the Ranggeh River segment from February to August 2019. A sampling of benthic macroinvertebrates was carried out using a Hess sampler on the riffle. This study shows that predators, shredders, and scrapers are still dominant when the Ranggeh River ecosystem is still minimally disturbed by agricultural activities and settlements. However, when agriculture activities and human settlements become more massive, the dominant FFGs are collector-filterers and collector-gatherers. Sedimentation parameters (turbidity and % embeddedness) in the Ranggeh River greatly influence predators, scrapers, and shredders. FFG has excellent potential to be further developed in preparing biocriteria for the effects of agriculture and human settlements.